2020
DOI: 10.1002/14651858.cd011621.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Personal protective equipment for preventing highly infectious diseases due to exposure to contaminated body fluids in healthcare staff

Abstract: Personal protective equipment for preventing highly infectious diseases due to exposure to contaminated body fluids in healthcare staff. Cochrane Database of Systematic Reviews, 2019(7), [CD011621].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
180
1
21

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 351 publications
(232 citation statements)
references
References 204 publications
(3 reference statements)
4
180
1
21
Order By: Relevance
“…The significant number of health care workers dying globally due to COVID-19 exposure (Ehrlich, McKenney, & Elkbuli, 2020) highlights the need for more to be done internationally to ensure that sufficient personal protective equipment is available to protect health care professionals during future pandemics. In addition to addressing supply issues, clearly communicated and evidence-based principles around recommended personal protective equipment use will ensure the prudent use of available supplies (Verbeek et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The significant number of health care workers dying globally due to COVID-19 exposure (Ehrlich, McKenney, & Elkbuli, 2020) highlights the need for more to be done internationally to ensure that sufficient personal protective equipment is available to protect health care professionals during future pandemics. In addition to addressing supply issues, clearly communicated and evidence-based principles around recommended personal protective equipment use will ensure the prudent use of available supplies (Verbeek et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…11 In a randomized controlled trial, it was reported that long aprons caused less contamination than protective suits and that the suits were particularly uncomfortable during putting on and removing. 12 Taking into account the risks that may occur as a result of healthcare workers' exposure to the virus, all units that perform diagnosis, treatment and care applications may need personal protective equipment of different characteristics according to the nature and disease of the patient that is treated. This equipment that is used must be in compliance with the standards.…”
Section: Introductionmentioning
confidence: 99%
“…The use of clothing should include: microparticulated respirators (N95 authenticated by the National Institute for Occupational Safety and Health or FFP2-standard respirators set by the European Union as an equivalent to N95) combined with wearable facial transparent screens and disposable water-resistant shoes, hair and full body covers [44,45].…”
Section: Considerations or Recommendations For Effective Delivery Of mentioning
confidence: 99%